1994
DOI: 10.1364/ao.33.005715
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the possibilities of remote laser sensing of fish schools

Abstract: The operation of an airborne lidar intended for the detection of fish schools is numerically simulated by the Monte Carlo method. The calculations are performed for schools located at small depths in order to study the regularities in the shaping of the lidar return accurately. Three models of the phase function of scattering of laser radiation in sea water are used. The signals reflected from surface waters that contain a school of fish are determined as a function of the lidar parameters, light scattering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…One straightforward technique is Monte Carlo, in which a large number of individual photons are tracked through random paths based on the statistical properties of the medium. [30][31][32] Starting at the surface and continuing at each scattering event, random numbers determine the distance and direction to the next event. For the distance, l, a random number is selected from the probability-density function.…”
Section: Basic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One straightforward technique is Monte Carlo, in which a large number of individual photons are tracked through random paths based on the statistical properties of the medium. [30][31][32] Starting at the surface and continuing at each scattering event, random numbers determine the distance and direction to the next event. For the distance, l, a random number is selected from the probability-density function.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…58 This early work demonstrated that lidar could be useful for fisheries applications, and this has been confirmed by several subsequent analyses. 32,59,60 The easiest case is when large fish are widely separated, so individuals can be seen in the return and counted. As an example, Fig.…”
Section: Fisheriesmentioning
confidence: 99%
“…Blue-green light propagates to depths up to 100 m (Squire and Krumboltz, 1981) and green lasers have been applied in the form of lidar (light detection and ranging), where photon backscatter is collected from light reflecting off biological targets in the water column. Although numerical algorithms for lidar detection of fish were established more than 20 years ago (Murphree et al, 1974), modelling of signal-to-noise ratio, estimation of fish abundance, and statistical treatment of lidar data is a continuing area of research (Krekova et al, 1994;Mitra and Churnside, 1999;Lo et al, 2000). Target strength is a function of green-light reflectivity and has been measured on frozen samples of several fish species (Churnside and McGillivary, 1991), and live sardines in a tank experiment (Churnside et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The reflection that lidar obtains from a school of fish must be processed to obtain quantities proportional to the number of fish within the depth resolution. This issue has been considered before (Krekova et al, 1994, Churnside and Hunter, 1996, Churnside et al, 1997, although conversion into biomass requires species identification and experimental knowledge of fish reflectivity and size.…”
Section: Discussionmentioning
confidence: 99%
“…As it can be operated from a small aircraft, it is an accessible tool to survey shallow coastal waters. Processing the lidar signal to obtain quantities proportional to the number of fish within the operational depth range has been demonstrated, although conversion into biomass requires species identification and experimental knowledge of fish reflectivity and size (Churnside and McGillivray, 1991;Krekova et al, 1994;Churnside and Hunter, 1996;Churnside et al, 1997). In this context, to improve estimation of recruitment at age 0 of the pelagic resources in the Atlantic waters of the Iberian Peninsula and the Bay of Biscay, a research project named ''Experimental Surveys for the Assessment of Juveniles'' (JUVESU-FAIR CT97-3374) was developed.…”
Section: Introductionmentioning
confidence: 99%